2007
DOI: 10.1097/01.brs.0000255202.94153.ca
|View full text |Cite
|
Sign up to set email alerts
|

Postural Changes of the Dural Sac in the Lumbar Spines of Asymptomatic Individuals Using Positional Stand-Up Magnetic Resonance Imaging

Abstract: A significant posture-dependent difference of the dural sac cross-sectional area at the level of intervertebral disc in asymptomatic volunteers has been demonstrated. When the posture changed from supine to standing position, lumbar dural sac volume expanded by the increased pressure of cerebrospinal fluid, and the dural sac cross-sectional area increased. The smallest values were found in the supine position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 7 publications
1
52
0
Order By: Relevance
“…Hirasawa et al [33] reported that with a posture change from the supine to standing and sitting flexed positions, lumbar dural sac volume expanded and the dural sac cross-sectional area increases in adults. They cited the reason as an increased pressure of cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Hirasawa et al [33] reported that with a posture change from the supine to standing and sitting flexed positions, lumbar dural sac volume expanded and the dural sac cross-sectional area increases in adults. They cited the reason as an increased pressure of cerebrospinal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…The images were part of a dataset that had been acquired for a previous study (13). Approval from a local Research Ethics Committee had been obtained and all subjects had given their informed consent.…”
Section: Subjectsmentioning
confidence: 99%
“…Lumbar cerebrospinal fluid pressure and dural-sac cross sectional area are smallest in the recumbent versus upright positions. 24,25 The dural bulging that is seen in the sitting position, 26 as compared with the lateral or prone positions, has been observed to decrease the force required to puncture the dura with a 17-gauge Tuohy needle. 27 Hence, the lateral position may decrease the possibility of inadvertent dural puncture.…”
Section: Introductionmentioning
confidence: 96%